Increased expression of Rab5A predicts metastasis and poor prognosis in colorectal cancer patients - Yu, Min-Hao (Int J Clin Exp Pathol, 2015)
Rab5A is reported to correlate with cancer development and progression. The purpose of this study is to explore the association between Rab5A expression and the clinical characteristics of colorectal cancer (CRC). Data containing three independent investigations from Oncomine database demonstrated that Rab5A is overexpression in CRC compared with normal tissue, similar result was also found in 32 matched CRC tissue samples by qPCR. The protein expression of Rab5A was examined in 390 CRC specimens and the results showed that high expression of Rab5A was significantly correlated with tumor size (P = 0.008), serum CEA (P = 0.002), liver metastasis (P = 0.014) and clinical stage (P = 0.010). Kaplan-Meier method suggested that overexpression of Rab5A protein expression had shorter overall survival times in CRC patients (P < 0.001). Multivariate Cox regression analysis confirmed Rab5A expression, tumor size and clinical stage as independent prognostic factor in CRC. In conclusion, the data indicated that higher expression of Rab5A was observed in CRC tissues and Rab5A may be identified as a useful predictor of metastasis and prognosis for CRC.